Dylematy wychowania XXI wieku a rozwój zrównoważony - Anna Strumińska-Doktór (Studia Ecologiae et Bioethicae)
Among the contemporary dilemmas connected with the upbringing, the issue of responsibility for oneself, for others and for the environment in which we live is particularly important, therefore, upbringing cannot be separated from life. It can be interpreted as the entirety of human actions aimed at shaping a human being for responsible fulfillment of roles in family and society.